Method for detecting mercury ions by using mercury ion triggering type tellurium-based nano material oxidase and kit for detecting mercury ions by using mercury ion triggering type tellurium-based nano material oxidase
By preparing highly stable tellurium-based nanomaterials similar to oxidases, a signal amplification colorimetric sensor triggered by Hg2+ was constructed, solving the sensitivity and false judgment problems of mercury ion detection and achieving highly selective and rapid on-site detection.
Patent Information
- Application Number
- CN202511231565.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-31
- Publication Date
- 2026-01-16
AI Technical Summary
Existing technologies are insufficient to achieve highly sensitive and selective detection of trace mercury ions in water, and traditional colorimetric methods are prone to causing color lightening and misjudgment, failing to meet the needs of rapid on-site detection.
A highly stable and catalytically active mercury ion-triggered tellurium-based nanomaterial oxidase was prepared using a soft template method. A signal amplification colorimetric sensor based on Hg2+ triggering was constructed, utilizing the high affinity between Te and Hg to achieve specific recognition and signal amplification.
It achieves highly selective and sensitive mercury ion detection, enabling naked-eye interpretation through color changes. It is suitable for on-site testing, solves the problem of misjudgment in traditional colorimetric methods, and has the advantages of low cost, environmental friendliness, and fast response.
Smart Images

Figure HDA0005574016860000011 
Figure HDA0005574016860000021 
Figure HDA0005574016860000031
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials technology, and specifically relates to a method utilizing mercury ions (Hg) 2+ A method and kit for detecting mercury ions using trigger-type tellurium-based nanomaterial oxidases. Background Technology
[0002] Mercury ions (Hg) 2+ Hg, a highly toxic heavy metal pollutant, is widely found in industrial wastewater, mining, electronic waste, and coal combustion emissions. It is difficult to degrade in the environment and easily accumulates and amplifies through the food chain (e.g., through fish, shellfish, and other aquatic organisms). In particular, in anaerobic aquatic environments, Hg... 2+ It can be converted into the more toxic methylmercury by microorganisms and can enter the human body through drinking water or seafood, damaging the central nervous system, leading to cognitive impairment, motor incoordination, and causing damage to the kidneys, liver, and immune system. Extremely low concentrations of Hg... 2+ Exposure can also cause serious harm to human health. Therefore, it is crucial to achieve the monitoring of trace amounts of Hg in water. 2+ Accurate measurement of Hg is of great significance. Currently, Hg... 2+ The detection of Hg mainly relies on laboratory analytical methods such as spectrometry (atomic absorption spectroscopy, etc.), mass spectrometry (inductively coupled plasma mass spectrometry), and electrochemical analysis. These methods are used to detect Hg. 2+ While possessing high selectivity and sensitivity, accurate and reliable results, and the ability to perform qualitative and quantitative analysis, it also suffers from problems such as complex pretreatment, time-consuming and labor-intensive processes, reliance on expensive instruments, and difficulty in use for on-site monitoring and live cell detection. Therefore, it is necessary to develop a highly sensitive, highly selective Hg assay suitable for on-site detection. 2+ Rapid analysis methods have significant practical implications.
[0003] Nanozymes are a class of functional nanomaterials that combine the catalytic activity of natural enzymes with unique physicochemical properties. They can detect target analytes through catalytic colorimetric reactions, exhibiting unique advantages such as high selectivity and sensitivity, rapid response, and ease of operation in the field of colorimetric sensors, meeting the practical requirements of on-site detection. In recent years, the use of Hg... 2+ The specific binding interaction with noble metal nanozymes and chalcogen nanomaterials enabled the Hg nanozyme to achieve catalytic activity by inhibiting the nanozyme's catalytic activity. 2+ Detection. However, based on the aforementioned "signal suppression" mechanism, Hg detection... 2+ The technology has obvious limitations: firstly, quantitative detection mainly relies on spectrophotometer measurement, requiring the establishment of a standard curve; secondly, if Hg is detected by visual colorimetry... 2+Because the human eye has poor ability to distinguish between light and dark colors, misjudgment is very likely, limiting its application in rapid on-site detection. Therefore, there is an urgent need to develop new colorimetric sensors with signal amplification capabilities to achieve Hg... 2+ Highly efficient naked-eye detection.
[0004] Tellurium (Te) is a metalloid element, belonging to the chalcogen group along with selenium (Se). In recent years, Te has attracted considerable attention due to its unique photoelectric, thermal, catalytic, and biomedical properties. Studies have shown that Te has a significant effect on Hg... 2+ It has high affinity and selectivity, and can efficiently capture Hg through specific interactions. 2+ Its binding capacity is far higher than that of other common heavy metal ions. This property enables Te-based nanomaterials to bind Hg... 2+ The detection field holds immense application potential. However, compared to Se-based nanomaterials, which have been proven to possess peroxidase-like and oxidase-like activities, research on the enzyme-like catalytic properties of Te-based nanomaterials remains largely unexplored, severely hindering their development and application in heavy metal detection sensors. To further investigate the research and application of Te-based nanomaterials in the field of nanozymes, this invention successfully established a method for preparing stably dispersed functional tellurium nanoparticles using a soft template method. Simultaneously, based on Te and Hg... 2+ High affinity alters the composition and structural properties of tellurium nanoparticles, triggering their oxidase-like catalytic activity, and successfully constructing a Hg-based... 2+ A signal-amplified colorimetric sensor that triggers the catalytic activity of nano-tellurium oxidases, applied to Hg 2+ Qualitative and quantitative detection of Hg was performed, and a kit was developed for use in aquatic environments. 2+ The on-site detection successfully overcame the technical bottlenecks of existing Te-based nanomaterials, which suffer from single function and lack of enzyme-like activity, and pioneered the application of Te-based nanozymes in the new field of heavy metal ion detection. By constructing a dual-functional system of "specific recognition-signal amplification", it not only filled the theoretical gap in Te-based nanozyme research, but also provided a brand-new technical path and methodological system for the field of heavy metal detection. Summary of the Invention
[0005] To overcome the shortcomings and deficiencies of existing technologies, the primary objective of this invention is to provide a method utilizing mercury ions (Hg) 2+ A method for detecting mercury ions using trigger-type tellurium-based nanomaterials and oxidases. This method first uses an amphiphilic soft template with multiple functional groups (hydrophilic functional groups such as hydroxyl, carboxyl, and amino groups) and / or hydrophobic domains as a stabilizing and structure-directing agent to prepare highly stable and highly catalytically active Hg ions via a soft template method. 2+ A trigger-activated tellurium-based nanomaterial oxidase was developed; then, based on the high affinity between Te and Hg, mercury telluride was formed in one step to trigger the oxidase-like catalytic activity of tellurium nanomaterials. Using this as a probe, a Hg-based oxidase-like catalytic activity was successfully constructed.2+ A signal amplification colorimetric sensor that triggers nano-telluric acid oxidase to achieve Hg 2+ High selectivity and high sensitivity for rapid colorimetric detection.
[0006] Another object of the present invention is to provide a method for detecting mercury ions (Hg) using the above method. 2+ A reagent kit for Hg was developed based on the standard curve obtained by the above method; 2+ A portable detection kit (including a colorimetric card and pre-filled reagents) for detecting Hg in aquatic environments. 2+ On-site testing.
[0007] Another object of the present invention is to provide the above-described method and method for detecting mercury ions (Hg). 2+ The kits are used in fields such as biology, optics, electricity, magnetism and catalysis.
[0008] The objective of this invention is achieved through the following technical solution:
[0009] A method for detecting mercury ions using mercury ion-triggered tellurium-based nanomaterial-based oxidases includes the following steps:
[0010] (1) Preparation of mercury ion-triggered tellurium-based nanomaterial oxidases;
[0011] (2) Mercury ion detection using mercury ion-triggered tellurium-based nanomaterial oxidases.
[0012] The preparation of the mercury ion-triggered tellurium-based nanomaterial oxidase in step (1) is carried out according to the following steps: under the condition of a stabilizer, the reaction system of tellurium precursor solution and reducing agent solution undergoes a reduction reaction, and the reaction is allowed to stand in a water bath at 20-100℃ for 0.25-6.00h to obtain nano-tellurium, which is then separated by dialysis in a MwCO 8000Da dialysis bag for 12-72h to obtain a suspension of mercury ion-triggered tellurium-based nanomaterial oxidase; the molar concentration of tellurium precursor in the tellurium precursor solution in the reaction system is 1mmol / L-8mmol / L, and the molar concentration of reducing agent in the reducing agent solution in the reaction system is 6mmol / L-48mmol / L.
[0013] The tellurium precursor is sodium tellurite, telluric acid, or tellurium dioxide.
[0014] The reducing agent is ascorbic acid, sodium ascorbate, reducing sugar, polyphenols, hydrazine hydrate, or sodium borohydride.
[0015] The stabilizer is a surfactant containing hydroxyl, amino, carboxyl, carbonyl groups and hydrophobic regions, a polymer, a biological extract, carbon quantum dots, or a mixture of the above substances in any proportion; the biological extract is an animal extract, plant extract, or microbial extract, specifically including flavonoids, tannins, phenolic substances, sugars, biological macromolecular proteins, biological macromolecular polysaccharides, biological macromolecular protein and biological macromolecular polysaccharide complexes, and biological polymers.
[0016] The amount of stabilizer added to the reaction system is 250–1750 mg / L.
[0017] The tellurium precursor is sodium tellurite; the reducing agent is vitamin C; the stabilizer is a chitosan and carbon quantum dot complex, wherein the amount of chitosan added to the reaction system is 500 mg / L and the amount of carbon quantum dots added to the reaction system is 1250 mg / L; the molar concentration of the tellurium precursor in the tellurium precursor solution in the reaction system is 3 mmol / L, and the molar concentration of the reducing agent in the reducing agent solution in the reaction system is 24 mmol / L; the water bath static reaction temperature is 60℃ and the time is 0.5 h.
[0018] The carbon quantum dots are β-cyclodextrin-nitrogen-doped fluorescent carbon quantum dots (β-CD-N-CQDs), and their specific synthesis method is as follows: β-cyclodextrin, urea, and citric acid are weighed and mixed in a mass ratio of 1:1:1. Ultrapure water is added to dissolve each gram of β-cyclodextrin using 10 mL of ultrapure water. The resulting mixture is placed in a microwave oven and heated at 800 W for 5 min. Ultrapure water is added to re-dissolve the mixture, followed by centrifugation at 4 °C and 3824 × g for 10 min. The supernatant is collected, filtered through a 0.22 μm filter membrane, and the filtrate is freeze-dried under vacuum to obtain β-cyclodextrin-nitrogen-doped fluorescent carbon quantum dots.
[0019] Step (2) describes the use of mercury ion-triggered tellurium-based nanomaterials for mercury ion detection, which is specifically performed according to the following steps:
[0020] A. A suspension of mercury ion-triggered tellurium-based nanomaterial oxidase was reacted with Hg 2+ The solution was placed in a buffer system with a concentration of 0.2 mol / L and a pH of 2–10. After reacting for 2–20 min, an amine substrate solution was added. The resulting mixture was then incubated in a water bath at 20–60 °C for 9–20 min to generate a colored substance. The absorbance was measured to establish the relationship between the absorbance and Hg of mercury ion-triggered tellurium-based nanomaterials as the oxidase activity. 2+ The quantitative relationship of concentration in the mixed system; the concentration of the mercury ion-triggered tellurium-based nanomaterial oxidase suspension is 2.4–154.4 μg / mL; the Hg 2+The concentration in the mixed system was 12.5–150.0 μmol / L;
[0021] B. A suspension of mercury ion-triggered tellurium-based nanomaterial oxidase with a concentration of 2.4–154.4 μg / mL was placed together with the liquid analyte into a buffer system with a concentration of 0.2 mol / L and a pH of 2–10. After reacting for 2–20 min, an amine substrate solution was added. The resulting mixture was then incubated in a water bath at 20–60 °C for 9–20 min to generate a colored substance. The absorbance was measured. The absorbance value of the mercury ion-triggered tellurium-based nanomaterial oxidase activity established in step A above was compared with Hg. 2+ The quantitative relationship of concentration in the mixed system was used to calculate the Hg concentration in the mixed system. 2+ The concentration of Hg in the liquid analyte was further calculated. 2+ The concentration.
[0022] The buffer system mentioned in steps A and B is a sodium acetate buffer system, a sodium citrate buffer system, or a phosphate buffer system; the amine substrate is 3,3',5,5'-tetramethylbenzidine (TMB), 2,2-azido-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt (ABTS), or o-phenylenediamine (OPD).
[0023] The concentration of the mercury ion-triggered tellurium-based nanomaterial oxidase suspension in steps A and B is 38.6 μg / mL; the reaction time is 5 min; the pH of the buffer system is 4; the amine substrate solution is a 1.248 mmol / L solution of 3,3',5,5'-tetramethylbenzidine (TMB); the water bath reaction temperature is 30°C, and the water bath reaction time is 12 min.
[0024] The suspension, buffer system, and Hg of the mercury ion-triggered tellurium-based nanomaterial oxidase described in step A. 2+ The volume ratio of the solution to the amine substrate solution is 4:33:1:2; the absorbance of the mercury ion-triggered tellurium-based nanomaterial oxidase activity is related to Hg. 2+ The quantitative relationship of concentration in the mixed system is y = 0.0139x - 0.001, R 2 =0.99, y is the absorbance of mercury ion-triggered tellurium-based nanomaterial oxidase activity, and x is Hg 2+ The detection limit for the concentration in the mixed system was 2.72 μmol / L.
[0025] In step B, the volume ratio of the mercury ion-triggered tellurium-based nanomaterial oxidase suspension, buffer system, liquid analyte, and amine substrate solution is 4:33:1:2.
[0026] A kit for detecting mercury ions using the above method, comprising pre-filled reagents, a standard colorimetric card, and instructions for use; the pre-filled reagents include separately dispensed suspensions of mercury ion-triggered tellurium-based nanomaterial-based oxidases and Hg. 2+ Standards, acetate-sodium acetate buffer, and 3,3',5,5'-tetramethylbenzidine solution.
[0027] The above-mentioned method for detecting mercury ions using mercury ion-triggered tellurium-based nanomaterials-based oxidases has applications in the fields of heavy metal detection, biology, and catalysis.
[0028] The above-mentioned reagent kit for detecting mercury ions has applications in the fields of heavy metal detection, biology, and catalysis.
[0029] The present invention has the following advantages and beneficial effects compared with the prior art:
[0030] This invention successfully synthesizes highly stable and catalytically active Hg by using amphiphilic substances with multiple functional groups and / or hydrophobic domains as functionalized soft templates. 2+ This invention utilizes a trigger-activated tellurium nano-oxidase and systematically studies its catalytic properties, filling a theoretical gap in the research of Te-based nanomaterials in the field of nanozymes. Furthermore, this invention achieves this through "Hg 2+ The "trigger-catalytic activation" mechanism achieves the integration of "recognition-signal amplification" dual functions, and successfully constructs a Hg-based... 2+ Novel Hg that triggers the catalytic activity of nano-tellurium oxidases 2+ Colorimetric sensor. This sensor utilizes Hg... 2+ The specific binding of Te triggers a colorimetric reaction, forming a highly sensitive "signal-on" detection mode. Its detection sensitivity and anti-interference ability are significantly superior to traditional "signal suppression" methods, exhibiting a more significant visual resolution effect. This invention achieves naked-eye interpretation or instrumental quantitative and qualitative analysis through intuitive color changes (e.g., colorless → blue), solving the problem of misjudgment caused by color fading in traditional colorimetric methods. Furthermore, it eliminates the need for complex instruments, can be integrated into portable reagent kits, and is suitable for rapid detection in field and industrial settings. This invention not only fills the theoretical gap in the field of Te-based nanomaterials for nanozymes, but its "signal amplification" colorimetric strategy effectively solves the misjudgment problem caused by color fading in traditional colorimetric methods, providing a basis for Hg... 2+ This invention provides a completely new detection pathway. It also boasts advantages such as low cost, environmental friendliness, and rapid response, making it suitable not only for Hg... 2+ The detection provides a completely new technical approach, and its strategy of "metal ion triggering nanozyme activity" can also be extended to the detection of other heavy metal ions, which has important theoretical value and application prospects. Attached Figure Description
[0031] Figure 1 Chitosan-carbon quantum dot-nanotellurium D nanoparticles prepared with different Vc and Na2TeO3 concentrations H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), A 410 and A 490 The absorbance value and its ratio (D), fluorescence intensity value (E), and fluorescence emission spectrum (F) at the point.
[0032] Figure 2 Chitosan-carbon quantum dot-nanotellurium D-type nanoparticles prepared with different amounts of carbon quantum dots H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), A 410 and A 490 The absorbance value and its ratio (D), fluorescence intensity value (E), and fluorescence emission spectrum (F) at the point.
[0033] Figure 3 Chitosan-carbon quantum dot-nanotellurium D-type nanoparticles prepared for different Vc to Na2TeO3 ratios H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), A 410 and A 490 The absorbance value and its ratio (D), fluorescence intensity value (E), and fluorescence emission spectrum (F) at the point.
[0034] Figure 4 Chitosan-carbon quantum dot-nanotellurium D-type nanoparticles prepared for different reaction times H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), A 410 and A 490 The absorbance value and its ratio (D), fluorescence intensity value (E), and fluorescence emission spectrum (F) at the point.
[0035] Figure 5 Chitosan-carbon quantum dot-nanotellurium D-type nanoparticles prepared at different reaction temperatures H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), A 410 and A 490 The absorbance value and its ratio (D), fluorescence intensity value (E), and fluorescence emission spectrum (F) at the point.
[0036] Figure 6 Appearance images of nano-tellurium suspensions prepared for different template types.
[0037] Figure 7 D-type tellurium nanoparticles prepared for different template types HTotal light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), and absorbance of oxidase-like activity (D).
[0038] Figure 8 Appearance images of nano-tellurium suspensions prepared with different types of reducing agents.
[0039] Figure 9 D-type tellurium nanoparticles prepared for different types of reducing agents H Total light intensity (A), PDI, Zeta potential (B), UV-Vis absorption spectrum (C), and absorbance of oxidase-like activity (D).
[0040] Figure 10 For Hg 2+ In the presence of the chitosan-carbon quantum dot-nano tellurium suspension, the UV-Vis absorption spectrum (A) and the absorbance change curve over time (B) of the substrate TMB before and after catalysis.
[0041] Figure 11 For different pH (A), reaction temperature (B), TMB concentration (C), and chitosan-carbon quantum dot-nano tellurium concentration (D), Hg 2+ Absorbance values that trigger the catalytic activity of chitosan-carbon quantum dot-nano tellurium oxidase.
[0042] Figure 12 For Hg 2+ Apparent kinetics of chitosan-carbon quantum dot-nanotelluric acid oxidase in the presence of TMB; TMB test concentrations of 0.416–1.664 mmol / L (A), and Lineweaver-Burk plots of the double reciprocals of the Michaelis equation (B).
[0043] Figure 13 Absorbance values for the activity of chitosan-carbon quantum dot-nano tellurium oxidase under the influence of different types of metal ions.
[0044] Figure 14 In the presence of different types of metal ions, Hg 2+ Absorbance values that trigger chitosan-carbon quantum dot-nano tellurium oxidase activity.
[0045] Figure 15 For different concentrations of Hg 2+ Absorbance (A) and Hg of the triggering chitosan-carbon quantum dot-nano tellurium oxidase activity 2+ Linear relationship between absorbance values and chitosan-carbon quantum dot-nano tellurium oxidase activity (B).
[0046] Figure 16 Based on Hg 2+ Hg triggers chitosan-carbon quantum dot-nano tellurium oxidase activity 2+An image of the standard colorimetric card for a portable test kit. Detailed Implementation
[0047] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. To make the objectives and technical solutions of the present invention clearer, the present invention will be further described in detail below using chitosan containing abundant hydroxyl and amino groups and carbon quantum particles with surface passivation and heteroatom doping as functionalized soft templates. The equipment, instruments, and reagents used in the present invention are all commonly used in the art. It should be understood that the examples described herein are merely illustrative of the invention and are not intended to limit the invention.
[0048] The chitosan-carbon quantum dot-nanotellurium obtained in the following examples is the mercury ion triggered tellurium-based nanomaterial oxidase of the present invention.
[0049] Example 1: A method for preparing nano-tellurium.
[0050] Synthesis of β-cyclodextrin-nitrogen-doped fluorescent carbon quantum dots (β-CD-N-CQDs): 1 g each of β-cyclodextrin, urea, and citric acid were weighed into a 100 mL Erlenmeyer flask, and 10 mL of ultrapure water was added to dissolve them. The mixture was placed in the center of a microwave oven and heated at 800 W for 5 min. 10 mL of ultrapure water was added to re-dissolve the mixture, and then centrifuged at 3824 × g for 10 min at 4 °C. The supernatant was collected, filtered through a 0.22 μm filter membrane, and the filtrate was freeze-dried under vacuum to obtain β-CD-N-CQDs powder for later use.
[0051] Eight 100mL beakers were labeled 1-8 in sequence. β-CD-N-CQDs powder was dissolved in ultrapure water to obtain a 2.5 g / L carbon quantum dot solution. 5 mL of the carbon quantum dot solution was added to each of the eight 100mL beakers, followed by 3.125 mL of a 4 g / L chitosan solution. Then, 0.25, 0.50, 0.75, 1.00, 1.25, 1.50, 1.75, and 2.00 mL of a 100 mmol / L N2 solution were added, respectively. The Na₂TeO₃ solution was magnetically stirred until homogeneous. Then, 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, 2.1, and 2.4 mL of a 500 mmol / L vitamin C solution were added, respectively. Finally, each beaker was brought to a final volume of 25 mL with ultrapure water to obtain a mixed system (at this point, the molar ratio of vitamin C to Na₂TeO₃ in beaker 1 was 6 mmol / L: 1 mmol / L, and the molar ratio of vitamin C to Na₂TeO₃ in beaker 2 was 12 mmol / L). The molar concentration ratio of Vc to Na2TeO3 in beaker #3 was 18 mmol / L: 3 mmol / L; in beaker #4 it was 24 mmol / L: 4 mmol / L; in beaker #5 it was 30 mmol / L: 5 mmol / L; in beaker #6 it was 36 mmol / L: 6 mmol / L; and in beaker #7 it was 2 mmol / L. The molar ratio of Vc to Na2TeO3 was 42 mmol / L:7 mmol / L (the molar ratio of Vc to Na2TeO3 in beaker #8 was 48 mmol / L:8 mmol / L). The mixture was magnetically stirred until homogeneous, and then allowed to stand in a 60°C water bath for 0.5 h. Following this, it was cooled in an ice-water bath for 3 min and dialyzed through an 8000 Da regenerated cellulose dialysis bag for 24 h (with water changed every 2.5 h) to obtain a chitosan-carbon quantum dot-nanotellurium (CS-CQDs-TeNPs) suspension. Precipitation was found in the final suspensions obtained in beakers #5-8, and no further analysis was performed. The final suspensions obtained in beakers #1-4 were analyzed to determine their D... H Total light intensity, PDI, potential, UV-Vis spectrum, and fluorescence intensity. For example... Figure 1 As shown, when the molar concentration ratio of Vc:Na2TeO3 is 18 mmol / L:3 mmol / L, the chitosan-carbon quantum dot-nanotellurium particle D H The particles are small, have a concentrated size distribution, high electrostatic stability, and strong fluorescence. Therefore, this concentration was chosen for subsequent experiments.
[0052] Example 2: A method for preparing nano-tellurium.
[0053] The only difference compared to Example 1 is:
[0054] By controlling the molar ratio of Vc:Na2TeO3 in the mixed system to 18 mmol / L:3 mmol / L, and varying the addition amount of β-CD-N-CQDs in the mixed system to 0, 250, 500, 750, 1000, 1250, and 1500 mg / L, chitosan-carbon quantum dot-nanotellurium was prepared, and its D0.05 was determined. H Total light intensity, PDI, potential, UV-Vis spectrum and fluorescence intensity, such as Figure 2 As shown, when the amount of β-CD-N-CQDs added is 1250 mg / L, the D of chitosan-carbon quantum dots-nanotellurium... H The particles are small, have a relatively concentrated particle size distribution, high electrostatic stability, and the highest fluorescence intensity. Therefore, this addition amount was chosen for subsequent experiments.
[0055] Example 3: A method for preparing nano-tellurium.
[0056] The only difference compared to Example 1 is:
[0057] By controlling the concentration of Na₂TeO₃ in the mixed system to 3 mmol / L, the addition amount of β-CD-N-CQDs to 1250 mg / L, and varying the concentration of Vc in the mixed system to 6, 12, 18, 24, 30, and 36 mmol / L, chitosan-carbon quantum dot-nanotellurium was prepared, and its D₂O₃ content was determined. H Total light intensity, PDI, potential, UV-Vis spectrum and fluorescence intensity, such as Figure 3 As shown, when the Vc:Na2TeO3 concentration is 24:3, the D of chitosan-carbon quantum dots-nanotellurium... H The reactant ratio was chosen because it has the smallest particle size, the largest number of particles, the most concentrated particle size distribution, high electrostatic stability, and high luminescence intensity.
[0058] Example 4: A method for preparing nano-tellurium.
[0059] The only difference compared to Example 1 is:
[0060] Chitosan-carbon quantum dot-nanotellurium was prepared by controlling the molar ratio of Vc:Na2TeO3 in the mixed system to 24 mmol / L:3 mmol / L, the amount of β-CD-N-CQDs added to 1250 mg / L, and the reaction time to 0.25, 0.50, 1.00, 2.00, 4.00, and 6.00 h. Its Dc was then determined. H Total light intensity, PDI, potential, UV-Vis spectrum and fluorescence intensity, such as Figure 4 As shown, when the reaction time is 0.5 h, the D of chitosan-carbon quantum dots-nanotellurium... HThe minimum zeta potential and high fluorescence intensity indicate that under these reaction conditions, the reaction can be fully completed in 0.5 hours, and chitosan-carbon quantum dot-nanotellurium particles with small particle size, large number, high electrostatic stability, and strong fluorescence intensity can be prepared.
[0061] Example 5: A method for preparing nano-tellurium.
[0062] The only difference compared to Example 1 is:
[0063] Chitosan-carbon quantum dot-nanotellurium was prepared by controlling the molar ratio of Vc:Na2TeO3 in the mixed system to 24 mmol / L:3 mmol / L, the amount of β-CD-N-CQDs added to 1250 mg / L, the reaction time to 0.5 h, and the reaction temperature to 20, 25, 40, 60, 80, and 100 °C. Its Dc was then measured. H Total light intensity, PDI, potential, UV-Vis spectrum and fluorescence intensity, such as Figure 5 As shown, when the reaction temperature is 60℃, the D of chitosan-carbon quantum dots-nanotellurium... H The minimum value, high zeta potential, and high fluorescence intensity indicate that chitosan-carbon quantum dot-nanotellurium particles with small particle size, concentrated distribution, high electrostatic stability, and strong luminescence intensity can be prepared at 60℃.
[0064] Example 6: A method for preparing nano-tellurium.
[0065] The only difference compared to Example 1 is:
[0066] Chitosan-carbon quantum dot-nanotellurium was prepared by controlling the molar ratio of Vc:Na2TeO3 in the mixed system to 24 mmol / L:3 mmol / L, the amount of β-CD-N-CQDs added to be 1250 mg / L, the reaction time to be 0.5 h, and the reaction temperature to be 60 °C.
[0067] Example 7: A method for preparing nano-tellurium.
[0068] The only difference compared to Example 6 is:
[0069] Nanoscale tellurium was prepared by changing the template types to catechin extract (TP), polyethylene glycol 6000 (PEG6000), epigallocatechin gallate (EGCG), sodium lauryl sulfate (SDS), Pu-erh tea water extract (PECT), glucose (G), and bovine serum albumin (BSA). Figure 6As can be seen, among various templates such as TP, PEG6000, EGCG, SDS, PECT, G, and BSA, only the nanotellurium suspensions prepared by PECT, EGCG, and TP were clear and transparent. Therefore, these three were selected for subsequent colloidal chemical property analysis. Figure 7 As shown, the tellurium nanoparticles prepared by the three methods all exhibit small average hydration diameter, narrow particle size distribution, and high electrostatic stability. Furthermore, the tellurium nanoparticles prepared using each type of template all demonstrate Hg2+-triggered oxidase-like catalytic activity, with those prepared using PECT, TP, and EGCG templates exhibiting the highest catalytic activity.
[0070] Example 8: A method for preparing nano-tellurium.
[0071] The only difference compared to Example 6 is:
[0072] Nanoscale tellurium was prepared by changing the reducing agents to sodium ascorbate (VC-Na), glucose (G), and epigallocatechin gallate (EGCG). Figure 8 As can be seen, the nano-tellurium suspension prepared using VC-Na and G as reducing agents is clear and transparent; therefore, these two agents were subsequently selected for colloidal chemical property analysis. Figure 9 As shown, both methods produce tellurium nanoparticles with high electrostatic stability and concentrated particle size distribution. The tellurium nanoparticles prepared with VC-Na exhibit smaller average water content and diameter. Furthermore, tellurium nanoparticles prepared with various reducing agents all possess Hg... 2+ Triggered oxidase-like catalytic activity.
[0073] Example 9: Characterization of the chemical, basic and optical properties of chitosan-carbon quantum dot-nanotellurium colloid.
[0074] The average hydrodynamic particle size and Zeta potential of the chitosan-carbon quantum dot-nanotellurium prepared in Example 6 were characterized using dynamic light scattering and laser Doppler velocimetry. The colloidal chemical properties of the chitosan-carbon quantum dot-nanotellurium obtained in this invention were investigated. The results showed that the chitosan-carbon quantum dot-nanotellurium exhibited good water solubility, an average hydrodynamic diameter of 98.41 nm, a total light intensity of 155.80 kcps, a PDI of 0.59, a uniform unimodal particle size distribution, and a Zeta potential of 39.07 mV, demonstrating high electrostatic stability.
[0075] The morphology, surface functional group composition and structure, and crystal structure of the chitosan-carbon quantum dot-nanotellurium prepared in Example 6 were characterized using transmission electron microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The basic properties of the chitosan-carbon quantum dot-nanotellurium obtained in this invention were investigated. The results showed that the chitosan-carbon quantum dot-nanotellurium exhibited a near-spherical structure with good monodispersity and uniform particle size distribution. Gaussian fitting revealed that the actual average diameter of the chitosan-carbon quantum dot-nanotellurium was 2.7 ± 0.5 nm. The surface contained hydrophilic groups such as -OH, -NH2, and -C=O, indicating that it was an amorphous, zero-valent nanotellurium.
[0076] The characteristic absorption peaks and fluorescence intensity of the chitosan-carbon quantum dot-nanotellurium prepared in Example 6 were determined using ultraviolet-visible absorption spectroscopy and fluorescence spectroscopy to study the optical properties of the chitosan-carbon quantum dot-nanotellurium obtained in this invention. The results showed that the absorption of chitosan-carbon quantum dot-nanotellurium was mainly concentrated in the range of 200–600 nm, with a significant characteristic absorption peak at 3357 nm, primarily attributed to the n-π* transition of C=O in the carbon nucleus. Its fluorescence emission was excitation-dependent, with a maximum excitation wavelength of 370 nm and a maximum emission wavelength of 460 nm.
[0077] Example 10: Hg 2+ Triggering the oxidase-like activity of chitosan-carbon quantum dots-nanotellurium.
[0078] 50 μL of the chitosan-carbon quantum dot-nanotellurium (CS-CQDs-TeNPs) solution (concentration 77.2 μg / mL) prepared in Example 6 was mixed with 412.5 μL of sodium acetate buffer (0.2 mol / L, pH 4.0), and 12.5 μL of 2 mmol / L HgCl2 solution was added. The mixture was allowed to stand for 5 min, and then 25 μL of 4 g / L TMB chromogenic substrate solution was added. The reaction system was placed in a 30°C constant temperature water bath and allowed to stand for 12 min. After that, the mixture was placed in an ice bath for 3 min, and its UV-Vis absorption spectrum (scanning range 400-800 nm) was measured. The results are as follows. Figure 10 As shown, in Hg 2+ In the presence of Hg, chitosan-carbon quantum dots-nanotellurium can effectively catalyze the oxidation of TMB, exhibiting a strong absorption peak at 652 nm, indicating that Hg 2+ It can trigger oxidase-like activity in chitosan-carbon quantum dots-nanotellurium. Furthermore, the linear relationship of its enzyme-like catalytic activity curve is best within the time range of 9–15 min; therefore, 15 min was chosen as the Hg threshold. 2+ The reaction time that triggers the activity of chitosan-carbon quantum dot-nano tellurium oxidase.
[0079] Example 11: Hg 2+Optimization and evaluation of the activity of chitosan-carbon quantum dot-nano tellurium oxidase.
[0080] The only difference compared to Example 10 is:
[0081] (1) The concentration of TMB solution was controlled at 4 g / L, the concentration of chitosan-carbon quantum dot-nano tellurium solution was controlled at 77.2 μg / mL, the reaction time was controlled at 12 min, the reaction temperature was controlled at 30℃, and the pH of sodium acetate buffer solution (0.2 mol / L) was changed to 2, 3, 4, 5, 6, 7, 8, 9, and 10. Hg was measured. 2+ Triggered oxidase-like activity in chitosan-carbon quantum dots-nanotellurium nanoparticles. Results are as follows: Figure 11 As shown in Figure A, at pH 4.0, Hg 2+ The oxidase-like activity triggered by chitosan-carbon quantum dots-nanotellurium is the strongest.
[0082] (2) The pH of the sodium acetate buffer solution (0.2 mol / L) was controlled at 4, the concentration of the TMB solution was 4 g / L, the concentration of the chitosan-carbon quantum dot-nano tellurium solution was 77.2 μg / mL, the reaction time was 12 min, and the reaction temperature was changed to 20, 30, 40, 50, 60, 70, and 80 °C. Hg was measured. 2+ Triggered oxidase-like activity in chitosan-carbon quantum dots-nanotellurium nanoparticles. Results are as follows: Figure 11 As shown in B, at a reaction temperature of 30℃, Hg 2+ The oxidase-like activity triggered by chitosan-carbon quantum dots-nanotellurium is the strongest.
[0083] (3) The pH of the sodium acetate buffer solution (0.2 mol / L) was controlled at 4, the concentration of the TMB solution was 4 g / L, the reaction time was 12 min, and the reaction temperature was 30℃. The concentrations of the chitosan-carbon quantum dot-nano tellurium solution were changed to 2.41, 4.83, 9.65, 19.30, 38.60, 77.20, and 154.40 μg / mL, and Hg was measured. 2+ Triggered oxidase-like activity in chitosan-carbon quantum dots-nanotellurium nanoparticles. Results are as follows: Figure 11 As shown in C, when the concentration of the chitosan-carbon quantum dot-nanotellurium solution is 38.60 μg / mL, Hg 2+ The oxidase-like activity triggered by chitosan-carbon quantum dots-nanotellurium is the strongest.
[0084] (4) The pH of the sodium acetate buffer solution (0.2 mol / L) was controlled at 4, the concentration of the chitosan-carbon quantum dot-nano tellurium solution was 77.2 μg / mL, the reaction time was 12 min, the reaction temperature was 30℃, and the concentration of the TMB solution was changed to 0.5, 1, 2, 3, 4, 5, 6, 7, and 8 g / L. Hg was measured. 2+Triggered oxidase-like activity in chitosan-carbon quantum dots-nanotellurium nanoparticles. Results are as follows: Figure 11 As shown in D, when the concentration of TMB solution is 6 g / L (final concentration 1.248 mmol / L), Hg 2+ The oxidase-like activity triggered by chitosan-carbon quantum dots-nanotellurium is the strongest.
[0085] (5) The pH of the sodium acetate buffer solution (0.2 mol / L) was controlled at 4, the concentration of the chitosan-carbon quantum dot-nano tellurium solution was 38.6 μg / mL, and the reaction temperature was 30℃. The Hg levels were measured at different concentrations of TMB solution (0.5, 1, 2, 3, 4, 5, 6, 7, 8 g / L) within the reaction range of 1–30 min. 2+ The absorbance of the chitosan-carbon quantum dot-nanotellurium oxidase-like activity was used to calculate its K0. m V max Parameters such as [list of parameters] were used to evaluate its oxidase-like catalytic activity. The results are as follows: Figure 12 As shown, Hg 2+ The initial rate of oxidase-like catalysis triggered by chitosan-carbon quantum dot-nanotellurium gradually increased with increasing TMB concentration (0.416–1.456 mmol / L), conforming to the typical Michaelis-Menten equation. Figure 12 (A), but when the TMB concentration is increased to 1.664 mmol / L, its catalytic rate decreases with increasing TMB concentration. A double reciprocal plot of the initial catalytic rate and the reciprocal of the substrate concentration (0.624–1.248 mmol / L) shows a good linear relationship. Figure 12 B), obtained by calculating the intercept and slope of the linear equation fitted in the double reciprocal plot, Hg 2+ K-type oxidases triggered by chitosan-carbon quantum dots-nanotellurium nanoparticles m The value was 13 mmol / L, V max 5000(10) -8 M·min -1 ).
[0086] Example 12: Chitosan-carbon quantum dot-nano tellurium oxidase activity against Hg 2+ The selectivity.
[0087] The only difference compared to Example 10 is:
[0088] The concentration of the chitosan-carbon quantum dot-nano tellurium solution was controlled at 38.60 μg / mL, the pH of the sodium acetate buffer system was 4, the reaction time of tellurium with metal ions was 5 min, the concentration of TMB solution was 6 g / L, the reaction time in a constant temperature water bath was 12 min, the temperature was 30℃, and the type of metal ion was changed to Na. + K +Ca 2+ Mg 2+ Mn 2+ Cu 2+ Ba 2+ Cd 2+ Ni 2+ Co 2+ 、Sr 2+ Pb 2 + Hg 2+ Al 3+ Fe 3+ Cr 3+ The oxidase-like catalytic activity of chitosan-carbon quantum dots-nanotellurium was determined, and the results are as follows: Figure 13 As shown, only Hg 2+ It can significantly trigger the oxidase-like catalytic activity of chitosan-carbon quantum dots-nanotellurium, exhibiting catalytic activity against Hg. 2+ High selectivity.
[0089] Example 13: Hg 2+ Anti-interference analysis of the activity of chitosan-carbon quantum dot-nano tellurium oxidase.
[0090] The only difference compared to Example 10 is:
[0091] The concentration of the chitosan-carbon quantum dot-nano tellurium solution was controlled at 38.60 μg / mL, the pH of the sodium acetate buffer system was 4, the reaction time of tellurium with metal ions was 5 min, the concentration of TMB solution was 6 g / L, the reaction was carried out in a constant temperature water bath for 12 min at 30℃, and Hg was added simultaneously. 2+ and Na + K + Ca 2+ Mg 2+ Mn 2+ Cu 2+ Ba 2+ Cd 2+ Ni 2+ Co 2+ 、Sr 2+ Pb 2+ Al 3 + Fe 3+ Cr 3+ The oxidase-like catalytic activity of chitosan-carbon quantum dots-nanotellurium was determined by measuring metal ions, and the results are as follows: Figure 14 As shown, in the presence of various metal ions, Hg 2+The oxidase-like catalytic activity triggered by chitosan-carbon quantum dot-nanotellurium was 75.26%–101.36% of that of the positive control group, indicating that common metal ions have a significant impact on the colorimetric Hg sensing activity of chitosan-carbon quantum dot-nanotellurium. 2+ The detection interference was not significant.
[0092] Example 14: Based on Hg 2+ Colorimetric detection of Hg-induced oxidase activity triggered by chitosan-carbon quantum dots-nanotellurium nanoparticles 2+ .
[0093] The only difference compared to Example 12 is:
[0094] The controlled metal ion species is Hg 2+ Change Hg 2+ The oxidase-like catalytic activity of chitosan-carbon quantum dots-nanotellurium was determined by measuring the concentrations of 0, 0.39, 0.78, 1.56, 3.13, 6.25, 12.50, 18.75, 25.00, 31.25, 37.50, 43.75, 50.00, 75.00, 100.00, 125.00, and 150.00 μmol / L in the reaction system. The results are as follows: Figure 15 As shown: Hg 2+ The concentration (x, 18.75–75.00 μmol / L) in the reaction system showed a linear relationship with the absorbance (y) of the oxidase-like activity of chitosan-carbon quantum dots-nanotellurium. A linear curve was obtained by fitting: y = 0.0139x - 0.001, R0 2 =0.99. LOD is 2.72 μmol / L.
[0095] Example 15: Hg 2+ Development of a portable detection kit for triggering chitosan-carbon quantum dot-nano tellurium oxidase activity.
[0096] Based on Example 14, the types, uses and storage conditions of the relevant reagents, detection steps, result interpretation (visual colorimetry / spectrophotometry) and precautions are written in the paper instruction manual.
[0097] A suspension of a mercury ion-triggered tellurium-based nanomaterial oxidase (i.e., chitosan-carbon quantum dot-nanotellurium) at a concentration of 38.6 μg / mL and a mercury ion-triggered tellurium nanoparticle at a concentration of 3 mmol / L were prepared. 2+ The standard, 0.2 mol / L sodium acetate buffer (pH 4.0), and 6 g / L TMB colorimetric reagent solution were packaged separately to form pre-packaged reagents, which were then packaged in light-proof aluminum foil tubes.
[0098] The standard colorimetric card was prepared as follows: 3 mmol / L Hg 2+Hg obtained after serial dilution of the standard 2+ The solutions were mixed with a mercury ion-triggered tellurium-based nanomaterial oxidase at a concentration of 38.6 μg / mL in sodium acetate buffer at pH 4.0, reacted for 5 minutes, and then a chromogenic reagent TMB solution at a concentration of 6 g / L was added to obtain 20–70 μmol / L Hg. 2+ A series of gradient concentration reaction systems were allowed to react in a 30°C water bath for 12 minutes before color development. The blue color gradient was photographed, printed onto a colorimetric card, and the corresponding Hg values were labeled. 2+ Actual concentration, such as Figure 16 As shown.
[0099] Finally, the above-mentioned paper instructions, aluminum foil-wrapped light-proof tubes containing reagents, and standard colorimetric cards were combined to form Hg. 2+ Portable detection kit for Hg in aquatic environments 2+ Rapid on-site testing.
[0100] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for detecting mercury ions by using mercury ion-triggered tellurium-based nanomaterials oxidase, characterized in that The method comprises the following steps: (1) preparation of mercury ion-triggered tellurium-based nanomaterial mimetic oxidase; (2) mercury ion detection by using the mercury ion-triggered tellurium-based nanomaterial mimetic oxidase. 2.The method for detecting mercury ions by using mercury ion-triggered tellurium-based nanomaterials according to claim 1, characterized in that: In the step (1), the mercury ion-triggered tellurium-based nanomaterial mimetic oxidase is prepared by the following steps: the tellurium precursor solution and the reducing agent solution are subjected to a reduction reaction in the presence of a stabilizer, and the reaction system is placed in a water bath at 20-100 ℃ for 0.25-6.00 h to obtain nanotellurium, and the nanotellurium is separated by dialysis in an MwCO 8000 Da dialysis bag for 12-72 h to obtain a suspension of the mercury ion-triggered tellurium-based nanomaterial mimetic oxidase; the molar concentration of the tellurium precursor in the reaction system is 1 mmol / L-8 mmol / L, and the molar concentration of the reducing agent in the reaction system is 6 mmol / L-48 mmol / L.
3. The method for detecting mercury ions by using the mercury ion-triggered tellurium-based nanomaterial mimetic oxidase according to claim 2, characterized in that: the tellurium precursor is sodium tellurite, telluric acid or tellurium dioxide; the reducing agent is ascorbic acid, sodium ascorbate, a reducing sugar, a polyphenol, hydrazine hydrate or sodium borohydride; the stabilizer is a surfactant containing a hydroxyl group, an amino group, a carboxyl group, a carbonyl group and a hydrophobic region, a high-molecular polymer, a biological extract, a carbon quantum dot or a mixture of the above substances in any proportion; the biological extract is an animal extract, a plant extract or a microbial extract, and specifically includes flavonoids, tannins, phenols, sugars, biological macromolecular proteins, biological macromolecular polysaccharides, biological macromolecular protein and polysaccharide complexes and biological polymers; the amount of the stabilizer added to the reaction system is 250-1750 mg / L. 4.The method for detecting mercury ions by using mercury ion-triggered tellurium-based nanomaterials according to claim 2, characterized in that: the tellurium precursor is sodium tellurite; the reducing agent is vitamin C; the stabilizer is a chitosan and carbon quantum dot complex, wherein the amount of chitosan added to the reaction system is 500 mg / L, the amount of carbon quantum dots added to the reaction system is 1250 mg / L; the molar concentration of the tellurium precursor in the reaction system is 3 mmol / L, and the molar concentration of the reducing agent in the reaction system is 24 mmol / L; the temperature of the water bath is 60 ℃, and the reaction time is 0.5 h. 5.The method for detecting mercury ions by using mercury ion-triggered tellurium-based nanomaterials according to claim 1, characterized in that: In the step (2), the mercury ion detection by using the mercury ion-triggered tellurium-based nanomaterial mimetic oxidase is carried out by the following steps: A, the suspension of mercury ion triggered tellurium-based nanomaterials oxidase is put into a buffer system with a concentration of 0.2 mol / L and a pH of 2-10 2+ After 2-20 min, an amine substrate solution is added, the obtained mixed system is placed in a water bath at 20-60 DEG C for 9-20 min to generate a colored substance, the absorbance is measured, and the absorbance of the mercury ion triggered tellurium-based nanomaterials oxidase activity is established with the Hg 2+ The concentration of the mercury ion triggered tellurium-based nanomaterials oxidase in the mixed system is 2.4-154.4 μg / mL; the concentration of the Hg 2+ The concentration of the mercury ion triggered tellurium-based nanomaterials oxidase in the mixed system is 2.4-154.4 μg / mL; the concentration of the Hg B, the suspension of mercury ion triggered tellurium-based nanomaterials oxidase with a concentration of 2.4-154.4 μg / mL is placed in a buffer system with a concentration of 0.2 mol / L and a pH of 2-10, and then an amine substrate solution is added after 2-20 min of reaction, and the obtained mixed system is placed in a water bath at 20-60℃ for 9-20 min to generate a colored substance, and the absorbance is measured, and the absorbance of the mercury ion triggered tellurium-based nanomaterials oxidase activity is calculated according to the above step A, and the concentration of Hg 2+ in the mixed system is calculated according to the quantitative relationship between the concentrations in the mixed system. 2+ The concentration of Hg 2+ in the liquid to be tested is further calculated. 6.The method for detecting mercury ions by using mercury ion-triggered tellurium-based nanomaterials according to claim 5, characterized in that: In the steps A and B, the buffer system is a sodium acetate buffer system, a sodium citrate buffer or a phosphoric acid buffer; and the amine substrate is 3,3',5,5'-tetramethylbenzidine, 2.2-diazenium-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt or o-phenylenediamine. 7.The method for detecting mercury ions using mercury ion-triggered tellurium-based nanomaterials according to claim 5, characterized in that: The concentration of the suspension of the mercury ion triggered tellurium-based nanomaterial mimetic oxidase in steps A and B is 38.6 μg / mL; the action time is 5 min; the pH of the buffer system is 4; the amine substrate solution is a 3,3',5,5'-tetramethylbenzidine solution with a concentration of 1.248 mmol / L; the temperature of the water bath standing reaction is 30℃, and the water bath standing reaction time is 12 min; The volume ratio of the mercury ion triggered tellurium-based nanomaterials oxidase suspension, buffer system, Hg 2+ solution, amine substrate solution in step A is 4:33:1:2; the absorbance value of the mercury ion triggered tellurium-based nanomaterials oxidase activity and Hg 2+ The quantitative relationship of the concentration in the mixed system is y=0.0139x-0.001, R 2 =0.99, y is the absorbance value of the mercury ion triggered tellurium-based nanomaterials oxidase activity, x is Hg 2+ The concentration in the mixed system, the detection limit is 2.72 μmol / L; In step B, the volume ratio of the suspension of the mercury ion triggered tellurium-based nanomaterial mimetic oxidase, the buffer system, the liquid to be tested, and the amine substrate solution is 4:33:1:
2.
8. A kit for detecting mercury ions using the method of any one of claims 1-7, wherein: The kit comprises preloaded reagents, standard colorimetric card and operation instruction; the preloaded reagents include respectively packaged suspension of mercury ion triggered tellurium-based nanomaterials oxidase, Hg 2+ standard, acetic acid-sodium acetate buffer and 3,3',5,5'-tetramethylbenzidine solution.
9. The use of the method for detecting mercury ions by using the mercury ion triggered tellurium-based nanomaterial mimetic oxidase according to claim 1 in the fields of heavy metal detection, biology, and catalysis.
10. The use of the kit for detecting mercury ions according to claim 8 in the fields of heavy metal detection, biology, and catalysis.